Peran Pelatihan dan Pengembangan Karyawan dalam Meningkatkan Kompetensi SDM di PT Timah Tbk - Fong, Claudia Putri; Fajrullah, Fauzan; Nabila, Agnes (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the role of employee training and development in improving human resource (HR) competency at PT Timah Tbk. Using a qualitative approach and literature study method, this study collected secondary data from various sources such as journals, articles, and company reports related to HR training. The results of the study indicate that the training program at PT Timah Tbk has a positive impact on improving employee technical and managerial skills. However, there are several obstacles that hinder the effectiveness of training, such as limited facilities and less than optimal evaluation. Therefore, the company needs to conduct continuous evaluation and improvement of the training program to achieve maximum results. This study provides insight into the importance of proper training management to improve HR competency in supporting the company's success.